Efforts to Increase Awareness of Saving Culture among Students at Budisatrya High School in Medan - Nasib; Tambunan, Debora; Roni Juliansyah; Emma Novirsari; Nidya Banuari; Steven Gea; Dewi Rafiah Pakpahan; Deby Siska Oktavia Pasaribu; Tony Honkley; Hamjah Arahman (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2024)
To increase the involvement of lecturers in society and ensure that universities function as agents of positive change, the government encourages lecturers to be actively involved in community service activities through the Tri Dharma program of higher education. In the community service program, lecturers are expected to provide their knowledge and expertise to the broader community and ensure that the knowledge produced is valuable and relevant for the benefit of human life. Lecturers and teams from Mahkota Tricom Unggul University carried out community service activities by providing material exposure related to fostering a culture of saving for students who are in high school. Fostering a culture of saving has many essential benefits both for individual development and society as a whole. By providing exposure to this culture of saving, the participants began to understand and understand the benefits gained from activities in getting used to saving. This activity is inseparable from the role and support of parents and teachers at school.